Second Hankel Determinants and Fekete-Szegö Inequalities for Some Sub-Classes of Bi-Univalent Functions with Respect to Symmetric and Conjugate Points Related to a Shell Shaped Region (Analysis in Theory and Applications, 2018)
In this paper, we have investigated second Hankel determinants and Fekete-Szegöinequalities for some subclasses of Bi-univalent functions with respect to symmetric and Conjugate points which are subordinate to a shell shaped region in theopen unit disc ∆.
Keywords: Analytic functions; univalent functions; Bi-univalent functions; second Hankel determinants; Fekete-Szegö inequalities; symmetric points; conjugate points.